Characteristics and Outcome of Partial Liver Transplant among Pediatrics in a Referral Transplant Center in Iran from 2010 to 2020 - Pooya Vatankhah; Mohammad Bagher Khosravi; Mohammad Hossein Eghbal; Naeimehossadat Asmarian; Mohammad Ali Sahmeddini; Fatemeh Khalili; Samaneh Ghazanfar Tehran; Hamed Nikoupour; Alireza Shamsaeefar; Kourosh Kazemi; Sahar Sohrabi Nazari; Saman Nikeghbalian; et al. (Iranian Journal of Medical Sciences, 2025)
Background: Liver transplantation (LT) is a critical intervention for pediatric patients with advanced liver failure. This study aimed to assess the impact of perioperative factors on LT outcomes in pediatric patients.Methods: This retrospective cohort study, conducted from 2010-2020, included 563 pediatric patients who underwent LT in Shiraz, Iran. Most patients received liver grafts from living donors due to cholestatic and metabolic diseases, and all had complete medical and laboratory records. Data were analyzed using various regression models (Cox, linear, and logistic) in SPSS software (version 22).Results: Of the 563 patients who underwent LT, 436 received livers from living donors and 127 from deceased donors. The primary diagnoses included cholestatic diseases (44.4%) and metabolic diseases (34.1%). Post-transplant rejection and mortality rates were 21.1% (119 patients) and 36.1% (203 patients), respectively. Preoperative factors associated with rejection included weight (HR=1.01, P=0.01) and albumin (HR=0.69, P=0.03). Postoperative factors influencing rejection included platelet transfusion (HR=2.12, P=0.03), primary non-function (PNF) (HR=4.6, P=0.01), cytomegalovirus (CMV)(HR=1.78, P=0.005), and convulsion (HR=1.93, P=0.007). Preoperative factors that affect mortality were age (HR=0.89, P<0.001), alanine aminotransferase (ALT) (HR=1, P=0.047), and hemoglobin levels (HR=0.91, P=0.03). Intraoperative factors influencing mortality included cold ischemia duration (HR=0.98, P=0.048) and anhepatic blood loss (HR=1.02, P<0.001). Postoperative factors associated with mortality included fresh frozen plasma (FFP) transfusion (HR=1.7, P=0.004), bleeding (HR=2.17, P=0.009), bowel perforation (HR=2.55, P=0.01), and PNF (HR=11.24, P<0.001). Conclusion: Optimizing perioperative care practices could significantly improve LT outcomes in pediatric patients.